Supplements as symbols: Public arguments against natural health product regulation in Canada - Colleen Derkatch; Julie Homchick Crowe (Elsevier, 2023)
After Canadian lawmakers proposed legislation in 2008 to better enforce existing regulations of the supplement industry, Canadians mounted significant public protest, including an online petition that garnered more than 24,000 signatures and 8585 comments over several months. In this article, we offer a rhetorical analysis of a randomized sample of those comments to track the range of topics and arguments advanced by signatories against the legislation. We identify five primary topics that recur throughout the dataset, freedom, choice, health, greed, and nature, which in turn furnish sixteen core arguments that together illuminate the signatories' primary concerns about potentially losing access to supplements. Ultimately, the topics and arguments reveal deep and persistent public anxieties not only about individuals' health but also about their agency and autonomy. This study both provides insight into why people reject government oversight of health in favor of alternative, natural health interventions and illustrates the utility of qualitative analysis of public commentary about health and health policy in texts such as petitions, public comment periods, and social media responses, all of which are rich sites of discourse that merit further study from both scholars, policy-makers, and health researchers and practitioners.